Classification of acrobatic movements of group P - "platforms" and their varieties in artistic swimming - Anastasiya Petrenko (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to classify and determine the methodology for constructing the technical value of acrobatic movements of "group P". Material and methods: theoretical analysis and generalization of scientific and methodological literature data, analysis of competition results, polls, methods of mathematical statistics. The competitive programs of the World and European Championships (2009-2021) and the Olympic Games (2008-2021) are analyzed. Results: analyzing the performances of leading athletes at the Olympic Games, World and European Championships, from 2004 to 2021, we developed a diagram where we can determine what platforms are performed least of all in comparison with other groups. The next step we have combined the existing types of acrobatic movements of "group P" into a single table, forming the criterion for assessing the "area of support" or "value of the type of connection" (grip). In total, the value of 30 types of connections was calculated in the group P - "platforms". Taking into account all the data obtained, a matrix was built, an algorithm for calculating the technical value of the "group P". Based on the developed methodology for calculating the technical value of acrobatic movements, a unified table (scale) of the technical value of acrobatic movements of "group P" was developed - a platform where acrobatic movements were distributed in order from the easiest to the most difficult according to the calculated technical value. Conclusions: the data of our research made it possible to create the author's system of classification of acrobatic movements, sort it out in detail and develop a methodology for determining and calculating the technical value of 81 acrobatic movements of "group P". The obtained data became the basis for the development of a unified table of the technical value of acrobatic movements of "group P" in artistic swimming. Preliminary approbation of this system and their discussion at international seminars of specialists, coaches and judges of various qualifications in artistic swimming made it possible to make a number of clarifications, additions and improve the development of a classification system for acrobatic movements of "group P" and an assessment of their complexity.